The song of the Doto (Nudibranchia: Dotidae): newly documented diversity from the coast of California - Adayapalam, Sneha; Bonomo, Lynn J.; Shipman, Carissa; Gosliner, Terrence M. (Zootaxa, 2025)
Two new species of Doto (Heterobranchia: Dotidae) are described from the coast of California, Doto urak Gosliner & Adayapalam sp. nov. and Doto kwakwak Gosliner & Adayapalam sp. nov. These two species can be distinguished from their sympatric congeners by their color pattern, elaboration of the cerata and associated structures, their reproductive morphology and molecular data. Both are members of the Pacific and southern Atlantic clade of species, detected previously by molecular phylogenetic methods. Previous findings about reproductive specializations in Doto, particularly in the Pacific and southern Atlantic clade, are tested and were supported by the addition of new members to this clade. More systematic and molecular phylogenetic work still needs to be undertaken with Doto to fully understand species richness, diversification, and biogeographical relationships.